An assessment of the quality and content of information on diverticulitis on the internet. Issue 6 (December 2018) - Connelly, Tara M.; Khan, Mohammad Shoaib; Victory, Liana; Mehmood, Abeera; Cooke, Fiachra
Abstract: Aim: Although commonly the first port of call for medical information, the internet provides unregulated information of variable quality. We aimed to evaluate commonly accessed web-based patient information on diverticulitis using validated and novel scoring systems. Methods: The top internet search engines (Google/Bing/Yahoo) were queried using the keyword 'diverticulitis.' The first 20 websites from each were graded using the DISCERN and Journal of the American Medical Association (JAMA) benchmark criteria. A novel diverticulitis-specific score was devised and applied. Results: Thirty-six unique websites were identified. The mean total DISCERN score for all websites was 39.92 ± 12.44 (range = 18–62). No website achieved the maximum DISCERN score of 75. The mean JAMA and diverticulitis scores were 2.5 ± 1.08 (maximum possible score = 4) and 11.08 ± 4.17 (19 points possible) respectively. Fourteen (35.9%) and 20 (51.2%) did not provide the date of last update and authorship respectively. Thirty-three (84.6%) mentioned surgery as a treatment option; however, the majority (69.7%) did not describe the surgery or the possibility of a stoma. All except two described disease symptoms. Only ten (25.64%) provided information on when to seek further medical advice or help. Conclusion: Web-based information on diverticulitis is of variable content and quality. The majority of top websites describe disease symptoms and aetiology; however, information to prompt seeking medical attention if required, descriptions of surgical procedures and the possibility of stoma creation are poorly described in the majority of websites. These findings should be highlighted to patients utilising the internet to obtain information on diverticulitis.